2004
DOI: 10.5483/bmbrep.2004.37.6.691
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interleukin 10 Haplotype with Low Bone Mineral Density in Korean Postmenopausal Women

Abstract: Osteoporosis is a disease characterized by exaggerated loss of bone mass, with as much as 50 to 85% of the variation in bone mineral density (BMD) commonly accepted as being genetically determined. Although intensive studies have attempted to elucidate the genetic effects of polymorphisms on BMD and/or osteoporosis in several genes, the genes involved are still largely unknown. The possible associations of genetic variants in five-candidate genes (IL10, CCR3, MCP1, MCP2 and GC) with spinal BMD were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Previous studies observed the opposite with IL-10. Byung Lae Park et al [43] found some connection of IL-10 haplotype with the reduced BMD in Korean postmenopausal women accompanied by the reduction of BMD. But the relationship between IL-10 and BMD was still not explained completely.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies observed the opposite with IL-10. Byung Lae Park et al [43] found some connection of IL-10 haplotype with the reduced BMD in Korean postmenopausal women accompanied by the reduction of BMD. But the relationship between IL-10 and BMD was still not explained completely.…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have indicated that the polymorphisms of IL-10 gene, which may affect IL-10 production, are associated with reduced bone mineral density (BMD) in postmenopausal women who were prone to suffered from osteoporosis [35, 36]. However, serum levels of IL-10 are significantly lower in the postmenopausal osteoporotic patient than in postmenopausal healthy women [37].…”
Section: Il-10 and Bone Metabolismmentioning
confidence: 99%
“…PTHR1 has been associated with BMD by Scillitani et al [33] who demonstrated that the subjects bearing at least one (AAAG)6 allele in the P3 promoter of PTHR1 gene have a higher femoral neck (FN) BMD than those without, suggesting the variation in promoter activity of the PTHR1 gene may exert a relevant genetic influence on BMD. IL10 has been found to be associated with BMD by Park et al [16]. The investigators studied the possible associations of genetic variants in five-candidate genes with spinal BMD.…”
Section: Genes Containing Known Bmd-associated Polymorphismsmentioning
confidence: 99%